(untitled) (MMIT Proceedings, 2026)
This paper presents a smart waste management system based on IoT sensors and artificial intelligence technologies. The system is designed to monitor the fill level of waste containers in real time, transmit data to a central server, and optimize the waste collection process using AI algorithms. The proposed approach improves waste logistics efficiency, reduces transportation costs, and mitigates environmental impacts. The results demonstrate that the system outperforms traditional waste management methods.